Modernisasi Pedidikan Islam, Demokratisasi Pendidik An Islam, dan Civil Society Islam Dalam Pandangan Filsafat Pendidikan Islam - Nabila, Syifa; Utarie, Maryani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses modernization, democratization and civil society in Islamic education as an effort to answer the challenges of contemporary developments. The modernization of Islamic education aims to adapt the education system to advances in science and technology, so that it remains relevant to the needs of the times. The democraticization of Islamic education focuses on implementing democratic values such as justice, equality and participation in the education system, to overcome inequality and the marginalization of certain groups. Islamic education civil society involves the active role of the community in providing education through various organizations and non-governmental institutions. The philosophical basis of these three movements is the philosophy of Islamic education, which prioritizes the formation of people who are faithful, knowledgeable and devout, as well as adaptive to changing times. This research uses a qualitative approach with library methods to collect and analyze data from various sources. The research results show that modernization, democratization and civil society in Islamic education can improve the quality and relevance of Islamic education in the modern era.